1993
DOI: 10.1007/bf00058214
|View full text |Cite
|
Sign up to set email alerts
|

The role of eggs in mercury excretion by Quail Coturnix coturnix and the implications for monitoring mercury pollution by analysis of feathers

Abstract: : This paper describes differences in the excretion of methyl mercury between male and female Quail Coturnix coturnix after a single dose. Since feathers are often used to monitor mercury pollution it is important to take into account biases in feather mercury levels that may arise as a result of mercury loss through egg-laying. Evidence is presented to support the use of bird eggs to sample for environmental mercury contamination. Birds were monitored up to twelve weeks after administration. Mercury concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…We found female Dunlin to have significantly lower blood mercury concentrations than males attending the same nest, supporting the notion that females may transfer mercury into their eggs (Lewis and Furness 1993). Although Ackerman et al (2007) also found female American Avocet and Black-necked Stilt had lower blood mercury concentrations than males, we did not find a significant difference between unmated male and female Semipalmated Sandpiper.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found female Dunlin to have significantly lower blood mercury concentrations than males attending the same nest, supporting the notion that females may transfer mercury into their eggs (Lewis and Furness 1993). Although Ackerman et al (2007) also found female American Avocet and Black-necked Stilt had lower blood mercury concentrations than males, we did not find a significant difference between unmated male and female Semipalmated Sandpiper.…”
Section: Discussionsupporting
confidence: 72%
“…We predicted HY shorebirds to have lower blood mercury concentrations than AHY because HY birds are able to rapidly depurate mercury during juvenile feather growth (Fournier et al 2002). We expected breeding AHY females to have lower blood mercury concentrations than breeding AHY males because female birds are able to depurate mercury into the eggs they produce (Lewis and Furness 1993). Finally, we predicted there would not be a relationship between blood and feather mercury concentrations in AHY shorebirds because most of the mercury in feathers is reflective of the conditions where the feathers were grown, which is typically away from the breeding grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory dosing studies on mallards (Anas platyrhynchos), chickens (Gallus gallus), and Japanese quail (Coturnix coturnix) have demonstrated that egg mercury concentrations increase in a dose-dependent manner in response to increasing dietary methylmercury [8,19,20]. Mercury has been detected in eggs within 2 d of a single oral dose of methylmercury in chickens [19].…”
Section: Discussionmentioning
confidence: 96%
“…Concurrently, we tested the hypothesis that the major congener profiles (relative percent) did not differ between media types. Finally, we tested to see if there were differences in contaminant loads (muscle and liver) between male and female clapper rails since depuration to eggs/chicks is a well known elimination pathway for both Hg and PCB's in birds (Bargar et al 2001;Lewis and Furness 1993).…”
Section: Introductionmentioning
confidence: 99%